Comparison of the cytotoxicity of the medicinal plant Poincianella pyramidalis and the endophytic fungus Penicillium sp. in macrophages of the J774 lineage (Revista Brasileira de Plantas Medicinais, 2020)
The aim of the present study was to evaluate the cytotoxic activity in vitro of the ethanolic extract of the plant Poincianella pyramidalis and of ethyl acetate extracts from the fermentation broth of endophytic fungi Penicillium sp. isolated from P. pyramidalis. This was a basic in vitro experimental research with a quantitative approach. The research consisted of macroscopic analysis assays associated with microscopic analysis to identify the taxonomy of isolated fungi as well as cell viability assay to evaluate the cytotoxic activity by the colorimetric method Methyltetrazolium (MTT) with macrophages of the J774 lineage. In the cytotoxic assay, the two extracts tested with the J774 macrophages strain proved to be non-toxic in all concentrations tested (100, 10 e 1 μg/mL). It is concluded that the medicinal plant P. pyramidalis harbor endophytic fungi Penicillium sp. and the fungal extract and ethanolic extract of the plant that were tested did not present deleterious effects to J774 macrophages.